GEOCAP :Geothermal capacity building program (Indonesia - Netherlands) - Meer, Freek van der (2020)
The dynamic growth and ambitious plans of the geothermal sector in Indonesia require a lot more skilled personnel and welltrained scientific specialists than currently exist hence a nation-wide capacity building program has been drafted by BAPPENAS. It is difficult to assess the capacity needed both in volume as well as in level of education. The Netherlands Embassy, through Agenschap.NL started to assist BAPPENAS in 2009, to accelerate investments in geothermal areas. In 2014 the NetherlandsIndonesian geothermal capacity building program GEOCAP was launched. The objective of the program is to increase the capacity of Indonesia’s Ministries, Local Government Agencies, public and private companies and knowledge institutions in developing, exploring and utilization of geothermal energy sources, and to assess and monitor its impact on the economy and environment. A broad Indonesian-Netherlands consortium consisting of 11 universities, knowledge institutes and geothermal companies formed a Public-Private Partnership to draft GEOCAP. The GEOCAP program has a number of intimately linked components: (1) an Education and training program; focusing on developing capacity at university and technician level in support of the development of the geothermal sector, (2) a research program; addressing the real needs of the sector and solving real life problems related to exploration, exploitation of geothermal resources as well as environmental and legislation issues, (3) a data base program; to collect, standardize, digitize and store surface and subsurface information relevant to geothermal development, (4) a program targeted to explore the use of-low & medium enthalpy resources in Indonesia and a (5) geothermal 2050 program aimed at out of the box thinking is necessary to explore potential unconventional geothermal resources that at present are undiscovered or technically not yet feasible. The GEOCAP progra